Society, polity, and economy of Bangladesh - Chakravarti, S. R. (New Delhi : Har-Anand Publications, 1994)
Comprises papers presented at the first and second sessions of seminar held on 7-8 March 1994.
Includes bibliographical references (p. [177]-178) and index.
Keywords: Bangladesh -- Politics and government -- 1971- -- Congresses; Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Social conditions -- Congresses